Neurological Complications after Lateral Transpsoas Approach to Anterior Interbody Fusion with a Novel Flat-Blade Spine-Fixed Retractor. (12th May 2016) - Nunley, Pierce; Sandhu, Faheem; Frank, Kelly; Stone, Marcus
Abstract : Introduction . The lateral lumbar interbody fusion (LLIF) surgical approach has potential advantages over other approaches but is associated with some unique neurologic risks due to the proximity of the lumbosacral plexus. The present study analyzed complications following LLIF surgical approach using a novel single flat-blade retractor system. Methods . A retrospective data collection of patients receiving LLIF using a novel single flat-blade retractor system at two institutions in the US. Inclusion criteria were all patients receiving an LLIF procedure with the RAVINE® Lateral Access System (K2M, Inc., Leesburg, VA, USA). There was no restriction on preoperative diagnosis or number of levels treated. Approach-related neurologic complications were collected and analyzed postoperatively through a minimum of one year. Results . Analysis included 253 patients with one to four treated lateral levels. Immediate postoperative neurologic complications were present in 11.1% (28/253) of patients. At one-year follow-up the approach-related neurologic complications resolved in all except 5 patients (2.0%). Conclusion . We observed an 11.1% neurologic complication rate in LLIF procedures. There was resolution of symptoms for most patients by 12-month follow-up, with only 2% of patients with residual symptoms. This supports the hypothesis that the vast majority of approach-related neurologic symptoms are transient.